Linagliptin provides effective, well‐tolerated add‐on therapy to pre‐existing oral antidiabetic therapy over 1 year in Japanese patients with type 2 diabetes. Issue 9 (3rd May 2013) - Inagaki, N.; Watada, H.; Murai, M.; Kagimura, T.; Gong, Y.; Patel, S.; Woerle, H.‐J.
<x xml:space="preserve">Abstract</x> Aims To evaluate the long‐term safety and efficacy of linagliptin as add‐on therapy to one approved oral antidiabetic drug (OAD) in Japanese patients with type 2 diabetes mellitus and insufficient glycaemic control. Methods This 52‐week, multicentre, open‐label, parallel‐group study evaluated once‐daily linagliptin 5 mg as add‐on therapy to one OAD [biguanide, glinide, glitazone, sulphonylurea (SU) or α‐glucosidase inhibitors (A‐GI)] in 618 patients. After a 2‐week run‐in, patients on SU or A‐GI were randomized to either linagliptin (once daily, 5 mg) or metformin (twice or thrice daily, up to 2250 mg/day) as add‐on therapy. Patients receiving the other OADs received linagliptin add‐on therapy (non‐randomized). Results Adverse events were mostly mild or moderate, and rates were similar across all groups. Hypoglycaemic events were rare, except in the SU group. Overall, 26 (5.8%) hypoglycaemic events were reported in patients receiving linagliptin (non‐randomized). Hypoglycaemic events were similar for linagliptin and metformin added to A‐GI (1/61 vs. 2/61, respectively) or SU (17/124 vs. 10/63, respectively). Significant reductions in glycated haemoglobin (HbA1c) levels (between −0.7 and −0.9%) occurred throughout the study period for the background therapy groups that received linagliptin (baseline HbA1c 7.9–8.1%). The decline in HbA1c levels was indistinguishable between linagliptin and metformin groups when administered as add‐on therapy to A‐GI or SU. Conclusions Once‐daily linagliptin showed safety and tolerability over 1 year and provided effective add‐on therapy leading to significant HbA1c reductions, similar to metformin, over 52 weeks in Japanese patients.